Case Report: Sarcoid-Like Reactions and Tertiary Lymphoid Structures Following Dual Checkpoint Inhibition in a Patient with Early-Stage Lung Adenocarcinoma - Zhao, Xiaoliang; Yue, Dongsheng; Qian, Juanjuan; Zhang, Lei; Song, Jin; Zhang, Bin; Zhang, Chunmei; Sun, Leina; Ma, Yuchen; Zhang, Henghui; Wang, Changli (Frontiers in Immunology, 2022)
Immune checkpoint inhibitor-induced sarcoid-like reactions and tertiary lymphoid structures (TLSs) are increasingly recognized but rarely reported in the same patient. We report a patient with lung adenocarcinoma who displayed sarcoid-like reactions in intrathoracic lymph nodes and tertiary lymphoid structures in surgical tumor after neoadjuvant therapy with nivolumab plus ipilimumab. Pathological examination revealed 50% residual tumor cells after treatment, and the CT evaluation of the primary tumor showed a stable disease. The patient experienced a recurrence eight months after surgery. To identify immune correlates of the limited response to immunotherapy, we conducted genomic and transcriptional assays, multiplex immunoassay, and multiplex immunohistochemistry on the pre- and post-immunotherapy tumor, lymph node, and plasma samples. TP53 R181C, KRAS G12C and SMAD4 R361H were identified as driver mutations of the tumor. In addition to abundant infiltrated lymphocytes, immunotherapy induced high levels of inhibitory components in post-treatment tissue samples, especially the FOXP3+ regulatory T cells in tumor and PD-L1 expression in the lymph node. Despite abundant TLSs in the post-treatment tumor, most TLSs were immature. Moreover, increasing levels of circulating checkpoint proteins BTLA, TIM-3, LAG-3, PD-1, PD-L1, and CTLA4 were observed during immunotherapy. Collectively, our observations revealed that high levels of immunosuppressive molecules in tumor, lymph nodes and/or in peripheral blood might indicate poor outcomes after immunotherapy, even in the setting of a patient with concurrent sarcoid-like reactions and tertiary lymphoid structures.